Sympatric kelp species share a large portion of their surface bacterial communities. (7th December 2017) - Lemay, Matthew A.; Martone, Patrick T.; Keeling, Patrick J.; Burt, Jenn M.; Krumhansl, Kira A.; Sanders, Rhea D.; Wegener Parfrey, Laura
Summary: Kelp forest ecosystems are biodiversity hotspots, providing habitat for dense assemblages of marine organisms and nutrients for marine and terrestrial food webs. The surfaces of kelps support diverse microbial communities that facilitate the transfer of carbon from algal primary production to higher trophic levels. We quantified the diversity of bacteria on the surfaces of eight sympatric kelp species from four sites in British Columbia. Kelp‐associated bacterial communities are significantly different from their environment, even though 86% of their bacterial taxa are shared with seawater and 97% are shared with rocky substrate. This differentiation is driven by differences in relative abundance of the bacterial taxa present. Similarly, a large portion of bacterial taxa (37%) is shared among all eight kelp species, yet differential abundance of bacterial taxa underlies differences in community structure among species. Kelp‐associated bacterial diversity does not track host phylogeny; instead bacterial community composition is correlated with the life‐history strategy of the host, with annual and perennial kelps supporting divergent bacterial communities. These data provide the first community‐scale investigation of kelp forest‐associated bacterial diversity. More broadly, this study provides insight into mechanisms that may structure bacterial communities among closely related sympatric host species.